Electrochemical sensor, preparation method thereof and method for detecting heavy metal ions in compound seasoning by using electrochemical sensor

By using nitrogen-doped carbon nanotubes to coat amino-functional alkaline MXene material and coat bismuth film composite electrode materials, the problem of insufficient selectivity and sensitivity of heavy metal ion detection in composite seasonings is solved, and efficient and reliable are achieved heavy metal ion detection.

CN119413865APending Publication Date: 2025-02-11ANHUI WANGXIAOLU BIOTECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411374479.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The prior art is difficult to detect a variety of heavy metal ions in composite seasonings quickly, sensitively and reliably, especially in complex food matrixes. The selectivity and sensitivity of the sensors are insufficient, and the long-term stability and batch reproducibility are not available. good.

Method used

The composite electrode material prepared by nitrogen-doped carbon nanotubes coated with amino-functionalized alkali MXene material can enhance the binding ability of MXene material with heavy metal ions through alkalization and amino-functionalization, improve the electron transfer efficiency of carbon nanotubes, and The enrichment of heavy metal ions is further promoted through bismuth film coating.

Benefits of technology

The good linear range, low detection limit, anti-interference ability, repeatability, stability and recovery of electrochemical sensors are achieved, providing a new strategy for the rapid detection of heavy metal ions in composite seasonings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119413865A_ABST
    Figure CN119413865A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of food detection. The invention provides an electrochemical sensor, a preparation method thereof and a method for detecting heavy metal ions in a compound seasoning by using the electrochemical sensor. An electrode material in the electrochemical sensor comprises a composite material obtained by coating an amino-functionalized alkaline MXene material with a nitrogen-doped carbon nanotube. The coordination of an MXene material and heavy metal ions is facilitated through alkalization and amino functionalization, the enrichment of the heavy metal ions is promoted, the electron transfer efficiency of the carbon nanotubes is improved through nitrogen doping, and active sites are provided for the heavy metal ions. The obtained composite material forms a three-dimensional stacked structure and a built-in electric field, provides a larger electrode surface area and stronger electron transfer capability, enhances the detection performance of the obtained electrochemical sensor, has a good linear range, lower detection limit and satisfactory anti-interference capability, repeatability, stability and recovery rate, and can be applied to the field of electrochemical sensors. A new strategy is provided for rapid detection of the heavy metal ions in the compound seasoning.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of food detection, and relates to an electrochemical sensor, a preparation method thereof and a method for detecting heavy metal ions in a composite seasoning. Background Art

[0002] As an indispensable part of modern cooking, compound seasonings are widely used in food cooking, seasoning and food processing (such as making casual marinated meat products). This type of seasoning usually uses at least two seasonings as raw materials, which are combined and proportioned by physical or biotechnological means to finally obtain various flavors to meet the diverse needs of consumers. Among the many ingredients of compound seasonings, spices occupy a pivotal position.

[0003] Spices are a type of natural plant-based raw materials with special aromas and flavors. There are many types of spices, including pepper, chili, garlic powder, onion powder, cloves, cinnamon, nutmeg and fennel. They not only add a unique flavor to food, but also have certain nutritional value and health functions. However, with the increasing prominence of food safety issues, the problem of heavy metal pollution in spices has gradually attracted people's attention.

[0004] Heavy metals refer to metals with a density greater than 4.5 g / cm 3 Metal elements such as lead, zinc, arsenic, cadmium, chromium, mercury, etc. are widely present in nature, but excessive intake can cause harm to human health. During the planting period, the roots of natural spices will absorb water and nutrients from the soil, and also absorb heavy metal elements in the soil. These heavy metals may come from the natural background value of the soil, industrial pollution, agricultural activities (such as the use of fertilizers, pesticides and water irrigation) and atmospheric deposition. Especially when the soil is polluted, the heavy metal content in spices will increase significantly.

[0005] In addition to absorption during planting, spices may also bring in heavy metals during processing. For example, in the drying, crushing, and packaging of spices, if the equipment or containers used contain heavy metal components, or the processing environment is contaminated by heavy metals, it may lead to an increase in the heavy metal content in the spices. In addition, some unscrupulous merchants may use additives or colorants containing heavy metals in order to reduce costs or improve the appearance of products, further exacerbating the problem of heavy metal pollution in spices. Moreover, due to the different parts of the spices used, there are significant differences in their heavy metal accumulation. Studies have shown that the heavy metal content in the roots and stems of spices grown in heavy metal-contaminated soil is often higher than that in the fruit part. For example, the roots and stems of chives (such as the white part of the green onion) are easy to absorb heavy metals. Therefore, chive powder is prone to high heavy metal content.

[0006] From the above, it can be seen that it is of great significance to establish a rapid, sensitive and reliable scheme for detecting multiple heavy metal ions in compound seasonings containing spices.

[0007] At present, heavy metal ions are mainly detected by large precision instruments, such as atomic absorption spectroscopy and inductively coupled plasma mass spectrometry (ICP-MS). However, these methods have disadvantages such as high cost, complicated operation and long time consumption. In contrast, electrochemical methods are not only simple to operate and low in cost, but also have the characteristics of fast response speed and high detection sensitivity.

[0008] As an important component of electrochemical sensors, electrode materials directly affect the detection performance of sensors. In complex food matrices, it is a challenge to improve the selectivity of sensors for specific heavy metals. At the same time, although electrochemical detection methods generally have higher sensitivity than other methods, they still need to be further improved to meet more stringent detection standards. The long-term stability and batch-to-batch reproducibility of sensors are key factors affecting their practical applications. Moreover, due to the complex composition of food matrices, the ability to detect multiple heavy metals simultaneously needs to be improved.

[0009] Therefore, designing electrode materials with excellent performance for the preparation of modified electrodes is the focus of research in this field, which is of great significance for promoting electrochemical metal ion detection of compound seasonings, preventing heavy metal pollution, meeting regulatory requirements, protecting consumer health, enhancing product competitiveness and promoting the healthy development of the industry. Summary of the invention

[0010] In view of the problems existing in the prior art, the object of the present invention is to provide an electrochemical sensor, a preparation method thereof and a method for detecting heavy metal ions in a composite seasoning, wherein the electrode material in the electrochemical sensor comprises a composite material obtained by coating an amino-functionalized alkaline MXene material with nitrogen-doped carbon nanotubes. Alkalization and amino-functionalization are beneficial to the coordination of MXene materials with heavy metal ions, promoting the enrichment of heavy metal ions, improving the electron transfer efficiency of carbon nanotubes by nitrogen doping, and providing active sites for heavy metal ions. The assembled composite material forms a three-dimensional stacking structure and a built-in electric field, providing a larger electrode surface area and a stronger electron transfer ability, further enhancing the detection performance of the obtained electrochemical sensor, so that it has a good linear range, a lower detection limit, and satisfactory anti-interference ability, repeatability, stability and recovery rate, providing a new strategy for the rapid detection of heavy metal ions in composite seasonings.

[0011] To achieve this object, the present invention adopts the following technical solutions:

[0012] In a first aspect, the present invention provides an electrochemical sensor, comprising an electrode substrate and an electrode material layer disposed thereon, wherein the electrode material of the electrode material layer comprises a composite material obtained by coating an amino-functionalized alkaline MXene material with nitrogen-doped carbon nanotubes.

[0013] MXene materials, such as Ti3C2T x MXene is a new type of multilayer two-dimensional nanomaterial with high specific surface area and modifiability, so it has attracted wide attention in the field of sensing. However, the interaction between MXene materials and heavy metal ions is weak, making it difficult to directly apply MXene materials to the electrochemical analysis of heavy metal ions. The present invention adopts alkalization and amino functionalization to enhance the binding ability of MXene materials with metal ions, especially the lone pair of electrons of the amino group can form a strong coordination effect with heavy metal ions to obtain modified MXene materials with better performance, which is beneficial to the coordination of MXene materials with heavy metal ions and promotes the enrichment of heavy metal ions; by nitrogen doping carbon nanotubes, the electron transfer efficiency of carbon nanotubes is improved, and active sites are provided for heavy metal ions. The composite material assembled by coating the amino functionalized alkaline MXene material with nitrogen-doped carbon nanotubes forms a three-dimensional stacking structure and a built-in electric field, providing a larger electrode surface area and a stronger electron transfer ability, further enhancing the detection performance of the obtained electrochemical sensor, so that it has a good linear range, a low detection limit, and satisfactory anti-interference ability, repeatability, stability and recovery rate. The invention provides a new strategy for the rapid detection of heavy metal ions in compound seasonings.

[0014] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0015] As a preferred technical solution of the present invention, the electrode material further includes a bismuth film, and the bismuth film covers the composite material.

[0016] The present invention obtains a modified electrode material by further coating the composite material with a bismuth film, so that the bismuth film can further promote the enrichment of heavy metal ions on the electrode surface by alloying with heavy metal ions. The electrochemical sensor based on the bismuth film can show a better linear detection range (for example, for Zn 2+ 0.045~1.000μM, for Cd 2+ 0.030~1.550μM, for Pb 2+ 0.025~1.950μM), lower detection limit (for example, for Zn 2+ is 15nM, for Cd 2+ 9.5nM for Pb 2+5nM), as well as better anti-interference ability, repeatability, stability and recovery rate.

[0017] Preferably, the electrode substrate comprises a glassy carbon electrode.

[0018] Preferably, the amino-functionalized alkaline MXene material comprises amino-functionalized alkaline Ti3C2T x .

[0019] In a second aspect, the present invention provides a method for preparing the electrochemical sensor according to the first aspect, the preparation method comprising:

[0020] (1) mixing and dispersing an amino-functionalized alkaline MXene material and nitrogen-doped carbon nanotubes in a medium solvent, so that the nitrogen-doped carbon nanotubes cover the amino-functionalized alkaline MXene material to generate a composite material, and obtaining a mixed dispersion;

[0021] (2) Using the mixed dispersion to form an electrode material layer on an electrode substrate to obtain an electrochemical sensor.

[0022] As a preferred technical solution of the present invention, the preparation method further includes, in step (1), first dispersing the nitrogen-doped carbon nanotubes in the medium solvent to obtain a dispersion liquid, and then adding the amino-functionalized alkaline MXene material to the dispersion liquid to perform the mixing and dispersion.

[0023] Preferably, the mass ratio of the nitrogen-doped carbon nanotubes to the amino-functionalized alkaline MXene material is (3-6):1, for example, 3:1, 3.2:1, 3.5:1, 3.8:1, 4:1, 4.2:1, 4.5:1, 4.8:1, 5:1, 5.3:1, 5.5:1, 5.8:1 or 6:1, etc.

[0024] Preferably, the medium solvent comprises N,N-dimethylformamide.

[0025] Preferably, the mixing and dispersing method comprises ultrasound, and the time is 50 to 70 min, for example, 50 min, 53 min, 55 min, 58 min, 60 min, 62 min, 65 min, 68 min or 70 min, etc.

[0026] Preferably, in the mixed dispersion, the mass concentration of the composite material is 0.8-1.2 mg / mL, for example, 0.8 mg / mL, 0.85 mg / mL, 0.9 mg / mL, 0.95 mg / mL, 1 mg / mL, 1.05 mg / mL, 1.1 mg / mL, 1.15 mg / mL or 1.2 mg / mL.

[0027] As a preferred technical solution of the present invention, the method for preparing the amino-functionalized alkaline MXene material in step (1) comprises providing an initial MXene material, first alkalizing the initial MXene material to obtain an alkaline MXene material, and then amino-functionalizing the initial MXene material to obtain an amino-functionalized alkaline MXene material;

[0028] Preferably, the initial MXene material comprises Ti3C2T x .

[0029] Preferably, the alkalization method comprises: first mixing and stirring the initial MXene material and the base in a first solvent, and performing a first washing and a first drying on the product to obtain the alkaline MXene material.

[0030] Preferably, the first solvent comprises water.

[0031] Preferably, the alkalization method further comprises: first preparing the first solvent and the base into an alkaline solution, and then performing the first mixing and stirring of the initial MXene material and the alkaline solution.

[0032] Preferably, the alkaline solution comprises a NaOH solution with a mass percentage concentration of 3% to 8%, for example, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5% or 8%.

[0033] Preferably, the temperature of the first mixing and stirring is 20-30°C, for example, 20°C, 22°C, 24°C, 26°C, 28°C or 30°C, and the time is 3-5h, for example, 3h, 3.3h, 3.5h, 3.8h, 4h, 4.2h, 4.5h, 4.8h or 5h.

[0034] Preferably, the first washing method comprises washing with the first solvent at least three times.

[0035] Preferably, the first drying method comprises vacuum drying at 40-60°C, for example, 40°C, 43°C, 45°C, 48°C, 50°C, 53°C, 55°C, 58°C or 60°C, for 8-12h, for example, 8h, 8.5h, 9h, 9.5h, 10h, 10.5h, 11h, 11.5h or 12h.

[0036] Preferably, the amino-functionalization method comprises performing a second mixing and stirring of the obtained alkaline MXene material and APTES in a second solvent, performing a second washing and a second drying of the product, to obtain an amino-functionalized alkaline MXene material.

[0037] In the present invention, the amino functionalization is preferably performed by using tris(3-aminopropyl)triethoxysilane (APTES), which is a widely used silicon coupling agent. In the present invention, it can graft amino groups on the surface of the material and minimize the damage to the material structure during the modification process. In addition, since APTES is grafted by reacting with hydroxyl groups, it is preferred to use APTES for amino functionalization after alkalization to modify more amino groups.

[0038] Preferably, the amino functionalization method further comprises first dispersing the obtained alkaline MXene material in a second solvent to obtain a suspension, and then adding the APTES suspension to the suspension to perform the second mixing and stirring.

[0039] Preferably, the amount of APTES is 0.1 to 0.5 mL per 25 mg of alkaline MXene material, for example, 0.1 mL, 0.15 mL, 0.2 mL, 0.25 mL, 0.3 mL, 0.35 mL, 0.4 mL, 0.45 mL or 0.5 mL.

[0040] Preferably, the second solvent comprises ethanol and / or water.

[0041] Preferably, the second solvent comprises ethanol and water in a volume ratio of (2-4):1, for example 2:1, 2.3:1, 2.5:1, 2.8:1, 3:1, 3.2:1, 3.5:1, 3.8:1 or 4:1, etc.

[0042] Preferably, the rotation speed of the second mixing and stirring is 400-600rpm, for example 400rpm, 420rpm, 450rpm, 480rpm, 500rpm, 530rpm, 550rpm, 580rpm or 600rpm, and the time is 15-25h, for example 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h or 25h, etc.

[0043] Preferably, the second washing method comprises washing at least five times using the second solvent.

[0044] Preferably, the second drying method comprises vacuum drying at 40-60°C, for example, 40°C, 43°C, 45°C, 48°C, 50°C, 53°C, 55°C, 58°C or 60°C, for 8-12h, for example, 8h, 8.5h, 9h, 9.5h, 10h, 10.5h, 11h, 11.5h or 12h.

[0045] As a preferred technical solution of the present invention, the method for preparing the nitrogen-doped carbon nanotubes in step (1) comprises: performing a third mixing and stirring of the carbon nanotubes and the nitrogen source in a third solvent to obtain a suspension, performing a hydrothermal reaction on the suspension, and performing a third washing and a third drying of the product to obtain the nitrogen-doped carbon nanotubes;

[0046] Preferably, the mass ratio of the carbon nanotubes to the nitrogen source is 1:(4-6), for example, 1:4, 1:4.3, 1:4.5, 1:4.8, 1:5, 1:5.3, 1:5.5, 1:5.8 or 1:6, etc.

[0047] Preferably, the nitrogen source comprises urea.

[0048] Preferably, the third solvent comprises water.

[0049] Preferably, the temperature of the third mixing and stirring is 20-30°C, for example, 20°C, 22°C, 24°C, 26°C, 28°C or 30°C, and the time is 30-60min, for example, 30min, 33min, 35min, 38min, 40min, 42min, 45min, 48min, 50min, 53min, 56min or 60min, etc.

[0050] Preferably, the temperature of the hydrothermal reaction is 160-180°C, for example, 160°C, 163°C, 165°C, 168°C, 170°C, 172°C, 175°C, 178°C or 180°C, and the time is 12-16h, for example, 12h, 12.5h, 13h, 13.5h, 14h, 14.5h, 15h, 15.5h or 16h, etc.

[0051] Preferably, the third washing method comprises washing at least five times using the third solvent.

[0052] Preferably, the third drying method comprises vacuum drying at 70-90°C, for example, 70°C, 73°C, 75°C, 78°C, 80°C, 83°C, 85°C, 88°C or 90°C, for 12-20h, for example, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h or 20h.

[0053] As a preferred technical solution of the present invention, the preparation method further comprises, in step (2), dropping the mixed dispersion onto the surface of the electrode substrate, drying it to form the electrode material layer, and obtaining the electrochemical sensor.

[0054] Preferably, the electrode substrate comprises a glassy carbon electrode.

[0055] Preferably, the glassy carbon electrode is polished and cleaned before use.

[0056] Preferably, the polishing and cleaning method includes first polishing the deerskin cloth with aluminum oxide powder having a particle size of 0.04 to 0.06 μM, for example, 0.04 μM, 0.043 μM, 0.045 μM, 0.048 μM, 0.05 μM, 0.052 μM, 0.055 μM, 0.058 μM or 0.06 μM, etc., and then ultrasonically cleaning with nitric acid and water having a mass percentage concentration of 40% to 60%, for example, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58% or 60%, etc.

[0057] Preferably, the drying temperature is 60-80°C, for example 60°C, 62°C, 65°C, 68°C, 70°C, 73°C, 75°C, 78°C or 80°C, and the drying time is 5-20min, for example 5min, 6min, 7min, 8min, 9min, 10min, 11min, 12min, 13min, 14min, 15min, 16min, 17min, 18min, 19min or 20min, etc.

[0058] As a preferred technical solution of the present invention, the preparation method also includes step (3), which includes using the electrochemical sensor obtained in step (2) as an initial electrode, electrochemically depositing the initial electrode in an electrolyte solution containing bismuth ions to generate a bismuth film and simultaneously coating the composite material to obtain an electrochemical sensor containing a bismuth film.

[0059] Preferably, in step (3), the electrolyte solution comprises an acetic acid buffer solution with a concentration of 0.1 to 0.3 mol / L, for example, 0.1 mol / L, 0.13 mol / L, 0.15 mol / L, 0.18 mol / L, 0.2 mol / L, 0.22 mol / L, 0.25 mol / L, 0.28 mol / L or 0.3 mol / L, etc.

[0060] Preferably, the concentration of bismuth ions in the bismuth ion-containing electrolyte solution is 0.6 to 3 mg / L, for example, 0.6 mg / L, 0.8 mg / L, 1 mg / L, 1.2 mg / L, 1.4 mg / L, 1.6 mg / L, 1.8 mg / L, 2 mg / L, 2.2 mg / L, 2.4 mg / L, 2.6 mg / L, 2.8 mg / L or 3 mg / L, etc., preferably 1.8 to 2.8 mg / L, and more preferably 2.2 to 2.6 mg / L.

[0061] Preferably, the electrochemical deposition method comprises differential pulse stripping voltammetry.

[0062] Preferably, the deposition potential range of the electrochemical deposition is -1.4 to -1.0 V, for example, -1.4 V, -1.38 V, -1.35 V, -1.32 V, -1.3 V, -1.28 V, -1.25 V, -1.22 V, -1.2 V, -1.17 V, -1.15 V, -1.13 V, -1.10 V, -1.07 V, -1.04 V or -1 V, etc., preferably -1.3 V to -1.1 V, and the deposition time is 100 to 800 s, for example, 100 s, 200 s, 300 s, 400 s, 500 s, 600 s, 700 s or 800 s, etc., preferably 300 to 750 s.

[0063] In a third aspect, the present invention provides a method for detecting heavy metal ions in a compound seasoning, wherein the detection method uses the electrochemical sensor described in the first aspect for detection, and the detection method comprises:

[0064] S1. After mixing the raw material sample of the composite seasoning with the digestion solution, digestion is performed to obtain a digestion solution;

[0065] S2. mixing the digestion solution with the electrolyte solution to obtain a solution to be tested;

[0066] S3. Using the electrochemical sensor as an electrode, a differential pulse stripping voltammetry test is performed in the solution to be detected to obtain a response signal of the target heavy metal ion.

[0067] As a preferred technical solution of the present invention, in step S1, the compound seasoning contains natural spices.

[0068] Preferably, the digestion solution comprises nitric acid and hydrogen peroxide in a volume ratio of (5-7):1, for example, 5:1, 5.3:1, 5.5:1, 5.8:1, 6:1, 6.2:1, 6.5:1, 6.8:1 or 7:1, etc.

[0069] Preferably, the mass percentage concentration of the nitric acid is 65% to 68%, for example, 65%, 65.5%, 66%, 66.5%, 67%, 67.5% or 68%; the mass percentage concentration of the hydrogen peroxide is 27.5% to 30%, for example, 27.5%, 28%, 28.5%, 29%, 29.5% or 30%.

[0070] Preferably, the amount of the digestion solution is controlled to be 10-20 mL per gram of the raw material sample of the composite seasoning, for example, 10 mL, 11 mL, 12 mL, 13 mL, 14 mL, 15 mL, 16 mL, 17 mL, 18 mL, 19 mL or 20 mL.

[0071] Preferably, the digestion method comprises microwave digestion.

[0072] Preferably, after the raw material sample of the compound seasoning is mixed with the digestion solution, it is first sealed and allowed to stand, and then the digestion is performed; the sealed and standing time is 6 to 24 hours, for example 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours or 24 hours, etc.

[0073] Preferably, the microwave digestion process comprises heating at 110-130°C, such as 110°C, 112°C, 115°C, 118°C, 120°C, 123°C, 125°C, 128°C or 130°C for 3-7 min, such as 3 min, 4 min, 5 min, 6 min or 7 min, and then heating at 140-160°C, such as 140°C, 143°C, 145°C, 148°C, 150°C, 152°C, 155°C, 158°C or 160°C for 8- The method comprises heating the mixture at a temperature of 180-200°C, for example, 180°C, 183°C, 185°C, 188°C, 190°C, 192°C, 195°C, 198°C or 200°C for 15-25 min, for example, 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, 21 min, 22 min, 23 min, 24 min or 25 min.

[0074] Preferably, in step S2, the electrolyte solution comprises an acetic acid buffer solution with a concentration of 0.1 to 0.3 mol / L, for example, 0.1 mol / L, 0.13 mol / L, 0.15 mol / L, 0.18 mol / L, 0.2 mol / L, 0.22 mol / L, 0.25 mol / L, 0.28 mol / L or 0.3 mol / L, etc.

[0075] Preferably, the volume ratio of the digestion solution to the electrolyte solution in the solution to be detected is 1:(20-30), for example, 1:20, 1:21, 1:22, 1:23, 1:24, 1:25, 1:26, 1:27, 1:28, 1:29 or 1:30, etc.

[0076] Preferably, in step S3, preferably, the detection potential range of the differential pulse stripping voltammetry test is -1.5 to 0 V, such as -1.5 V, -1.48 V, -1.45 V, -1.43 V, -1.4 V, -1.38 V, -1.35 V, -1.32 V, -1.3 V, -1.28 V, -1.25 V, -1.22 V, -1.2 V, -1.17 V, -1.15 V, -1.13 V, -1.10 V, -1.07 V, -1.04 V, -1 V, -0.9 V, -0.8 V, -0.7 V, -0.6 V, -0.5 V, -0.4 V, -0.3 V, -0.2 V, -0.1 V or 0 V, etc., preferably -1.25 to -0.4 V.

[0077] In the present invention, the detection potential range of electrochemical detection refers to monitoring different potential peaks within a range; the pulse amplitude and pulse period of the differential pulse stripping voltammetry test of electrochemical detection can be the instrument default values, such as the pulse amplitude is 0.05V, the pulse period is 0.5s, and the detection time is not specifically limited, and is based on the time used to detect the entire target potential range.

[0078] Preferably, the target heavy metal ions include Zn 2+ 、Cd 2+ or Pd 2+ At least one of .

[0079] It should be noted that the electrochemical sensor obtained by the present invention can also be used for the detection of heavy metal ions in solutions to be detected from other sources when the target heavy metal ion species, linear detection range and detection limit of the electrochemical sensor obtained by the present invention are met.

[0080] Compared with the prior art solutions, the present invention has at least the following beneficial effects:

[0081] The present invention facilitates the coordination of MXene materials with heavy metal ions through alkalization and amino functionalization, promotes the enrichment of metal ions, improves the electron transfer efficiency of carbon nanotubes through nitrogen doping, and provides active sites for metal ions. The assembled composite material forms a three-dimensional stacking structure and a built-in electric field, provides a larger electrode surface area and a stronger electron transfer ability, and further enhances the detection performance of the obtained electrochemical sensor, so that it has a good linear range, a lower detection limit, and satisfactory anti-interference ability, repeatability, stability and recovery rate, providing a new strategy for the rapid detection of heavy metal ions in compound seasonings.

[0082] The present invention obtains a modified electrode material by further coating the composite material with a bismuth film, so that the bismuth film can further promote the enrichment of heavy metal ions on the electrode surface by alloying with heavy metal ions. The electrochemical sensor based on the bismuth film can show a better linear detection range (for example, for Zn 2+ 0.045~1.000μM, for Cd 2+ 0.030~1.550μM, for Pb 2+ 0.025~1.950μM), lower detection limit (for example, for Zn 2+ is 15nM, for Cd 2+ 9.5nM for Pb 2+ 5nM), as well as better anti-interference ability, repeatability, stability and recovery rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0083] Figure 1a-Figure 1e The scanning electron microscope (SEM) test images of the electrode materials obtained in Comparative Examples 1-5 are respectively;

[0084] Figure 1f The composite material NH2-alk-Ti3C2T obtained in Example 1 x @Scanning electron microscope test image of N-CNTs;

[0085] Figure 1g for Figure 1f A magnified image of

[0086] Figure 1h The electrode material Bi / NH2-alk-Ti3C2T obtained in Example 2 x @EDS spectrum test chart of N-CNTs;

[0087] Figure 2a and Figure 2b It is a Fourier transform infrared spectrum (FTIR) test diagram of the electrode materials obtained in Comparative Examples 1-5 and Example 1;

[0088] Figure 2c and Figure 2d The X-ray diffraction (XRD) test diagrams of the electrode materials obtained in Comparative Examples 1-5 and Example 1;

[0089] Figure 3a and Figure 3b This is a total spectrum test diagram of the X-ray photoelectron spectroscopy (XPS) of the electrode materials obtained in Comparative Examples 1-5 and Example 1;

[0090] Figure 3c and Figure 3d The C1s spectrum test and fitting diagram of the X-ray photoelectron spectrum of the electrode materials obtained in Comparative Examples 1-5 and Example 1;

[0091] Figure 3e It is the O1s spectrum test and fitting diagram of the X-ray photoelectron spectrum of the electrode material obtained in Examples 1-3;

[0092] Figure 3f It is the N1s spectrum test and fitting diagram of the X-ray photoelectron spectrum of the electrode materials obtained in Comparative Examples 4 and 5 and Example 1;

[0093] Figure 3g and Figure 3h The X-ray photoelectron spectroscopy Ti2p spectrum test and fitting diagram of the electrode materials obtained in Comparative Examples 1-3 and Example 1;

[0094] Figure 4a This is a cyclic voltammetry (CV) test diagram of the electrochemical sensors obtained in Comparative Examples 1-6 and Example 1 as electrodes;

[0095] Figure 4b The Fe on the electrochemical sensor obtained in Example 1 2+ / Fe 3+ Dynamic characteristic test diagram at different scanning rates;

[0096] Figure 5 The electrochemical sensors obtained in Examples 1-6 and Examples 1-2 were used to simultaneously detect Zn 2+ 、Cd 2+ and Pb 2 + Performance evaluation test chart;

[0097] Figure 6a The electrochemical sensors obtained in Examples 3-6 respectively detect Zn 2+ 、Cd 2+ and Pb 2+ Performance evaluation test chart;

[0098] Figure 6b The electrochemical sensor obtained in Example 5 is used to simultaneously detect Zn in solutions to be detected at different pH values. 2+ 、Cd 2+ and Pb 2+ Performance evaluation test chart;

[0099] Figure 6c The electrochemical sensor obtained in Example 5 was used to simultaneously detect Zn at different deposition times. 2+ 、Cd 2+ and Pb 2+ Performance evaluation test chart;

[0100] Figure 6d The electrochemical sensor obtained in Example 5 was used to simultaneously detect Zn at different deposition potentials. 2+ 、Cd2+ and Pb 2+ Performance evaluation test chart;

[0101] Figure 7a The electrochemical sensor obtained in Example 5 contains different concentrations of Zn 2+ The solution to be tested was used to detect Zn 2+ Performance evaluation test chart;

[0102] Figure 7b The electrochemical sensor obtained in Example 5 contains different concentrations of Cd 2+ The solution to be tested was used to detect Cd alone 2+ Performance evaluation test chart;

[0103] Figure 7c The electrochemical sensor obtained in Example 5 contains different concentrations of Pb 2+ The solution to be tested is used to detect Pb alone 2+ Performance evaluation test chart;

[0104] Figure 7d The electrochemical sensor obtained in Example 5 simultaneously detects Zn 2+ 、Cd 2+ and Pb 2+ Performance evaluation test chart;

[0105] Figure 8a-8d The electrochemical sensor obtained in Example 5 simultaneously detects Zn 2+ 、Cd 2+ and Pb 2+ The performance reproducibility evaluation test chart, repeatability evaluation test chart, stability evaluation test chart and anti-interference evaluation test chart are included. DETAILED DESCRIPTION

[0106] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0107] Example 1

[0108] The present embodiment provides an electrochemical sensor, including an electrode substrate and an electrode material layer disposed thereon, wherein the electrode material of the electrode material layer is nitrogen-doped carbon nanotubes N-CNTs coated with amino-functionalized alkaline MXene material NH2-alk-Ti3C2T x The obtained composite material; the electrode matrix is ​​a glassy carbon electrode GCE.

[0109] The preparation method of the electrochemical sensor comprises:

[0110] (1) Preparation of amino-functionalized alkaline MXene material NH2-alk-Ti3C2T x :

[0111] First, 50 mg of Ti3C2T x The mixture was dispersed in 20 mL of 5% (w / v) NaOH solution and stirred at 25 °C for 4 h for alkalization. After the alkalization process was completed, the resultant was washed with ultrapure water for 3 times. Finally, the alkaline MXene material alk-Ti3C2T was obtained by vacuum drying at 50 °C for 10 h. x ;

[0112] 25 mg of alk-Ti3C2T x The powder was added to 10 mL of ethanol / H2O (3:1, v / v) solution. Then 0.2 mL of APTES suspension was added and stirred continuously at 500 rpm for 20 h to perform amino functionalization. Finally, it was washed with ethanol 5 times and then vacuum dried at 40 °C for 12 h to obtain amino functionalized alkaline MXene material NH2-alk-Ti3C2T x .

[0113] Preparation of nitrogen-doped carbon nanotubes N-CNTs:

[0114] First, 30 mg of carbon nanotubes (CNTs) and 150 mg of nitrogen source urea were added to 30 mL of ultrapure water and stirred at 25 °C for 45 min. The suspension was then transferred to an autoclave and subjected to a hydrothermal reaction at 170 °C for 14 h. Finally, the mixture was washed with ultrapure water 5 times and then vacuum dried at 80 °C for 16 h to obtain nitrogen-doped carbon nanotubes (N-CNTs).

[0115] Preparation of composite materials NH2-alk-Ti3C2T x @N-CNTs, and obtain a mixed dispersion:

[0116] First, 9 mg of N-CNTs were ultrasonically dispersed in 11 mL of N,N-dimethylformamide until a uniform solution was formed. x The nitrogen-doped carbon nanotubes are dispersed into the above solution, and then ultrasonically treated for 60 min to allow the amino-functionalized alkaline MXene material to be coated with the nitrogen-doped carbon nanotubes to generate a composite material NH2-alk-Ti3C2T x @N-CNTs, and obtain a mixed dispersion with a concentration of 1 mg / mL.

[0117] (2) Preparation of electrochemical sensor NH2-alk-Ti3C2T x @N-CNTs / GCE:

[0118] Prepare glassy carbon electrode GCE as the electrode substrate, use 0.05μM alumina powder to polish the glassy carbon electrode on suede, and then use 50% mass percentage concentrated nitric acid and ultrapure water to ultrasonically clean the GCE. x @N-CNTs was used as the electrode material. 1.3 μL of the prepared mixed dispersion was dropped on the GCE surface and dried in an oven at 70 °C for 10 min to form an electrode material layer. The electrochemical sensor NH2-alk-Ti3C2T x @N-CNTs / GCE.

[0119] Example 2

[0120] The present embodiment provides an electrochemical sensor, including an electrode substrate and an electrode material layer disposed thereon, wherein the electrode material of the electrode material layer includes nitrogen-doped carbon nanotubes N-CNTs coated with amino-functionalized alkaline MXene material NH2-alk-Ti3C2T x The obtained composite material also includes a bismuth film Bi, which covers the composite material; the electrode matrix is ​​a glassy carbon electrode GCE.

[0121] The method for preparing the electrochemical sensor further comprises step (3), wherein step (3) comprises:

[0122] Preparation of bismuth-containing electrochemical sensors (Bi / NH2-alk-Ti3C2T x @N-CNTs / GCE): The electrochemical sensor obtained in step (2) was used as the initial electrode, and differential pulse stripping voltammetry (DPSV) was performed in 0.2 mol / L acetic acid buffer solution (ABS) to electrochemically deposit a bismuth film. 3+ The initial concentration of 1.2 mg / L was set, and the initial parameters of DPSV were set to a deposition potential of -1.2 V and a deposition time of 150 s, generating a bismuth film and simultaneously coating the composite material to form an electrode material Bi / NH2-alk-Ti3C2T x @N-CNTs, obtained bismuth-containing film electrochemical sensor Bi / NH2-alk-Ti3C2T x @N-CNTs / GCE.

[0123] Except for the above, other conditions are exactly the same as those in Example 1.

[0124] Embodiment 3-6

[0125] Examples 3-6 provide an electrochemical sensor, respectively, wherein the thickness of the bismuth film in the electrochemical sensor is changed, that is, in step (3) of the preparation method of the electrochemical sensor, the Bi in the acetic acid buffer solution is changed to 3+The initial concentration of was adjusted from 1.2 mg / L to 0.6 mg / L, 1.8 mg / L, 2.4 mg / L and 3 mg / L respectively. Except for the above, other conditions are exactly the same as those in Example 1.

[0126] Comparative Examples 1-5

[0127] Comparative Examples 1-5 provide an electrochemical sensor, that is, the Ti3C2T x alk-Ti3C2T x 、NH2-alk-Ti3C2T x , CNTs or N-CNTs were used as electrode materials and ultrasonically dispersed in N,N-dimethylformamide, and then the dispersion was used to form an electrode material layer on GCE to obtain an electrochemical sensor, which was denoted as Ti3C2T x / GCE、alk-Ti3C2T x / GCE、NH2-alk-Ti3C2T x / GCE, CNTs / GCE and N-CNTs / GCE. Except for the above, other conditions are exactly the same as those in Example 1.

[0128] Comparative Example 6

[0129] Comparative Example 6 uses a blank GCE without an electrode material layer as an electrochemical sensor. Except for the above, other conditions are exactly the same as those of Example 1.

[0130] [Microstructure and morphology characterization]

[0131] Figure 1a-Figure 1e The scanning electron microscope (SEM) test images of the electrode materials obtained in Comparative Examples 1-5 are respectively; Figure 1a , Ti3C2T x It shows an obvious accordion-like structure, which provides a large surface area for subsequent material modification. After alkalization treatment, it can be observed that alk-Ti3C2T x The interlayer spacing ( Figure 1b ) is slightly reduced, which may be due to the alkalinization process of Ti3C2T x After amino functionalization, NH2-alk-Ti3C2T x ( Figure 1c ) shows a higher x The tighter layer structure may be attributed to the interlocking nanochannels of APTES. Figure 1d ), a typical one-dimensional tubular structure (diameter of about 30-45 nm) with interweaving and wrapping can be observed. After nitrogen doping, the microscopic morphology of N-CNTs ( Figure 1e )No significant changes.

[0132] Figure 1f and Figure 1g This is a scanning electron microscope test image of the composite material obtained in Example 1. It can be observed that in NH2-alk-Ti3C2T x In the N-CNTs composite material, N-CNTs are covered on NH2-alk-Ti3C2T x The surface forms a three-dimensional stacking structure, which can provide more metal ion binding sites and enhance the efficiency of electron transfer.

[0133] Figure 1h The EDS spectrum test diagram of the electrode material obtained in Example 2 shows that a small amount of Si and Bi elements can be observed on the electrode surface, which not only confirms the successful deposition of Bi film, but also indicates that NH2-alk-Ti3C2T x Successful preparation.

[0134] [Characterization of functional groups]

[0135] Figure 2a and Figure 2b The following is a Fourier transform infrared spectrum (FTIR) test diagram of the electrode materials obtained in Examples 1-5 and Example 1. x materials, strong peaks appear at 1637cm -1 、1217cm -1 and 565cm -1 , which are attributed to the vibration of C=O, CF and Ti-O respectively. x (alk-Ti3C2T x ), note that at 1371cm -1 A new absorption peak appeared at , which corresponds to the bending vibration of -OH, proving the successful modification of the hydroxyl group after alkalization. x , it can be observed at 897cm -1 A new absorption peak appeared at 1633 cm, corresponding to the vibration of Ti-O-Si, which is related to the grafting of APTES. -1 and 1020cm -1 The absorption peaks at are attributed to C=O in the carboxyl group and CO in the alkoxy group, respectively. x @N-CNTs, NH2-alk-Ti3C2T x The functional groups of N-CNTs and N-CNTs are present in the composites, confirming the successful preparation of the composites.

[0136] [Characterization of crystal structure and phase composition]

[0137] Figure 2c and Figure 2d The X-ray diffraction (XRD) test diagram of the electrode materials obtained in Examples 1-5 and Example 1 shows that Ti3C2T x The crystals of alk-Ti3C2T show sharp diffraction peaks, indicating good crystallinity. x and NH2-alk-Ti3C2T x XRD patterns of Ti3C2T x This indicates that the crystal structure is not completely destroyed during the modification process. It is worth noting that after alkalization and amino functionalization, the (002) plane at 9.22° gradually moves to a lower angle, which can be attributed to the intercalation of sodium ions and the grafting of APTES. Figure 2d , the peaks of CNTs are located at 25.92° and 43.72°, corresponding to the (002) and (101) planes, which are typical diffraction patterns of carbon nanotubes. For N-CNTs, the intensity of the diffraction peaks is enhanced compared with that of CNTs, which is caused by the improved crystallinity after nitrogen doping. x In the XRD spectrum of @N-CNTs, NH2-alk-Ti3C2T x and N-CNTs diffraction peaks, indicating that the crystal plane structures of the two single materials in the composite material are retained to a certain extent.

[0138] [Characterization of surface chemical structure]

[0139] Figure 3a and Figure 3b The X-ray photoelectron spectroscopy (XPS) of the electrode materials obtained in Examples 1-5 and Example 1 is a total spectrum test diagram; the figure shows that Ti3C2T x alk-Ti3C2T x 、NH2-alk-Ti3C2T x and NH2-alk-Ti3C2T x @F, O, Ti, N and C elements were found in N-CNTs, and O, N and C elements were found in CNTs and N-CNTs. x and NH2-alk-Ti3C2T x In addition to the above elements, Si element was also observed in @N-CNTs, proving that APTES was successfully grafted onto alk-Ti3C2T x surface.

[0140] Figure 3c and Figure 3d The X-ray photoelectron spectrum of the electrode materials obtained in Examples 1-5 and Example 1 is shown in the C1s spectrum test and fitting diagram; the figure shows that for Ti3C2T x alk-Ti3C2T x and NH2-alk-Ti3C2T x , the characteristic peaks in ascending order of binding energy correspond to C-Ti, C-Ti-O, CC, CO, and O=CO / CF bonds. For CNTs and N-CNTs, the characteristic peaks in ascending order of binding energy correspond to C=C, CO, C=O, O=CO, O=C-OH, and π-π* bonds. It is worth noting that NH2-alk-Ti3C2T x and N-CNTs exhibit new characteristic peaks corresponding to C-N bonds, which are due to the grafting of APTES and the doping of nitrogen atoms. x The C1s spectrum of @N-CNTs is consistent with that of N-CNTs, which is because N-CNTs cover the NH2-alk-Ti3C2T x surface.

[0141] Figure 3e The O1s spectrum test and fitting diagram of the X-ray photoelectron spectrum of the electrode materials obtained in Examples 1-3 are shown in the figure. x and alk-Ti3C2T x Four characteristic peaks are shown, corresponding to Ti-O, C-Ti-O, C=O and CO, arranged in ascending order of binding energy. x A new Ti-O-Si peak appeared.

[0142] Figure 3f The N1s spectrum test and fitting diagram of the X-ray photoelectron spectrum of the electrode materials obtained in Examples 4 and 5 and Example 1 are shown in the figure; the two characteristic peaks of carbon nanotubes are explained as pyrrole N and graphite N respectively. x @N-CNTs, they show characteristic peaks corresponding to pyridinic N, pyrrolic N, and graphitic N, indicating that the doping of nitrogen atoms leads to the generation of pyridinic N. In addition, the N1s spectrum intensity of N-CNTs is higher than that of CNTs, further confirming the successful doping of nitrogen atoms.

[0143] Figure 3g and Figure 3h The X-ray photoelectron spectroscopy Ti2p spectrum test and fitting diagram of the electrode materials obtained in Examples 1-3 and Example 1 are shown in the figure. x alk-Ti3C2T x、NH2-alk-Ti3C2T x and NH2-alk-Ti3C2T x The deconvolution of @N-CNTs includes four spin-orbit doublets (2p 3 / 2 -2p 1 / 2 ), which can be interpreted as Ti-C, Ti 2+ 、Ti 3+ and TiO2. It can be observed that alk-Ti3C2T x The peak intensity of TiO2 is higher than that of Ti3C2T x This may be due to the fact that Ti3C2T x It is worth noting that NH2-alk-Ti3C2T x The characteristic peak of N1s spectrum of @N-CNTs shifts to low binding energy, while that of NH2-alk-Ti3C2T x The characteristic peak of Ti2p spectrum of @N-CNTs shifts to high binding energy. This phenomenon may be due to the x The synergistic effect between the N and Ti atoms leads to an increase in the electron density of N atoms and a decrease in the electron density of Ti atoms. Therefore, it can be inferred that the composite material develops a built-in electric field, which improves the composite material NH2-alk-Ti3C2T x @N-CNTs’ electron transport capability.

[0144] [Electrochemical Characterization]

[0145] The electrochemical sensors obtained in Comparative Examples 1-6 and Example 1 were used as electrodes and respectively in 5.0 mM [Fe(CN)6] 3- / 4- In solution, the electrochemical properties were studied by cyclic voltammetry (CV), such as Figure 4a As shown in the figure, sorted by response current: Ti3C2T x / GCE<GCE<alk-Ti3C2T x / GCE<NH2-alk-Ti3C2T x / GCE<CNTs / GCE<N-CNTs / GCE<NH2-alk-Ti3C2T x @N-CNTs / GCE. The higher the response current of cyclic voltammetry, the faster the electron transfer rate of the electrode, so NH2-alk-Ti3C2T x @N-CNTs / GCE exhibits the best electron transport ability.

[0146] The reasons for the above phenomenon are as follows: Compared with other electrodes, Ti3C2T x / GCE has a lower cyclic voltammetric response current, which is due to the strong electronegativity of fluorine causing the Ti3C2T x The fluorine group of Ti3C2T4 has a low polarity, making it difficult to interact with hexacyanoferric ions. x The response current of / GCE is improved, which may be because the highly electronegative fluorine groups are replaced by less electronegative hydroxyl groups, forming a hydrophilic surface. x After amine functionalization, the obtained NH2-alk-Ti3C2T x The CV response current of / GCE is further improved because the electrostatic interaction between the positively charged amino groups and the negatively charged hexacyanoferrate ions promotes electron transfer. x Better electron transport capability, which can be attributed to its excellent electrical conductivity. In addition, the doping of nitrogen atoms makes N-CNTs have better dispersibility and electrical conductivity, further accelerating the charge transport on the electrode surface. x @N-CNTs / GCE exhibits the strongest electron transport capability, which is due to the formation of a built-in electric field in the composite material, which improves the electron transport rate.

[0147] In addition, the electrode surface area of ​​the electrochemical sensors obtained in Comparative Examples 1-6 and Example 1 was calculated according to the Randled-Sevcik equation. x / GCE, GCE, alk-Ti3C2T x / GCE、NH2-alk-Ti3C2T x / GCE, CNTs / GCE, N-CNTs / GCE and NH2-alk-Ti3C2T x The electrode surface areas of @N-CNTs / GCE are 0.036, 0.049, 0.054, 0.058, 0.059, 0.063, and 0.067 cm 2 The increase in electrode surface area means that more metal ion binding sites may be available, facilitating the binding and catalysis of target metal ions.

[0148] Figure 4b NH2-alk-Ti3C2T obtained in Example 1 x @N-CNTs / Fe on GCE 2+ / Fe 3+ Dynamic characteristics test diagram at different scan rates; the figure shows that with the increase of scan rate (10-300mV / s), the redox peak current increases significantly and is linearly positively correlated with the square root of the scan rate. This indicates that NH2-alk-Ti3C2Tx The redox process of @N-CNTs composites is diffusion controlled.

[0149] Application Example 1

[0150] This application example provides a method for detecting heavy metal ions, the detection method comprising:

[0151] Prepare a 0.2MABS solution containing heavy metal ions as the solution to be tested, the pH of the solution to be tested is 3-7, and the total concentration of heavy metal ions is 1-10 μM; use the electrochemical sensor as an electrode, perform DPSV test in the solution to be tested, set the detection potential to -1.4--0.4V, the pulse amplitude to 0.05V, the pulse period to 0.5s, and the deposition time to 100-800s to obtain the heavy metal ion response signal.

[0152] [Evaluation of detection performance of electrode composite modified materials]

[0153] According to the detection method of this application example, a sample containing heavy metal ions Zn 2+ or Cd 2+ or Pb 2+ The solution to be tested has a pH of 5 and a concentration of heavy metal ions of 10 μM. The electrochemical sensors of Examples 1-2 and Comparative Examples 1-6 were used as electrodes, respectively, and DPSV tests were performed in the solution to be tested, with the deposition potential set to -1.2 V, the pulse amplitude to 0.05 V, the pulse period to 0.5 s, and the deposition time to 150 s.

[0154] like Figure 5 As shown, in GCE, Ti3C2T x / GCE、alk-Ti3C2T x / GCE and NH2-alk-Ti3C2T x / Only Cd can be observed on GCE 2+ and Pb 2+ The response signals of Ti3C2T4 and Ti3C2T5 were observed on the other modified electrodes. x The response current of / GCE is lower, which is due to the x The electron transport ability of Ti3C2T is poor. x The fluorine groups on the surface inhibit the adsorption of heavy metal ions. x / GCE has an improved peak current, which is due to the conversion of Ti-F bonds to Ti-O bonds. x / GCE, the enhancement of peak current is because the amino group can bind to heavy metal ions through coordination bonds, thus contributing to the enrichment of metal ions. For CNTs / GCE, the response currents of the three target metal ions increased significantly, which is due to the excellent electrochemical properties of CNTs. For N-CNTs / GCE, its response current increased further compared with CNTs / GCE, which is because the nitrogen-doped atoms not only accelerate the charge transfer rate, but also serve as active sites for the target metal ions. Compared with the above-mentioned single material modified electrodes, NH2-alk-Ti3C2T x @N-CNTs / GCE showed a higher response current to the target metal ions. This is mainly due to the fact that NH2-alk-Ti3C2T x Synergistic effect between NH2-alk-Ti3C2T x The three-dimensional stacking structure of @N-CNTs increases the surface area and provides more binding sites; on the other hand, NH2-alk-Ti3C2T x A built-in electric field is formed between the Bi / NH2-alk-Ti3C2T x @N-CNTs / GCE has the strongest response signal.

[0155] [Evaluation of the influence of bismuth film thickness]

[0156] According to the detection method of this application example, a sample containing heavy metal ions Zn is prepared. 2+ or Cd 2+ or Pb 2+ The solution to be tested has a pH of 5 and a heavy metal ion concentration of 1 μM. The electrochemical sensors of Examples 3-6 were used as electrodes, respectively, and DPSV tests were performed in the solution to be tested, with the deposition potential set to -1.2 V, the pulse amplitude to 0.05 V, the pulse period to 0.5 s, and the deposition time to 700 s.

[0157] like Figure 6a As shown, with Bi 3+ As the concentration increased from 0.6 to 2.4 mg / L, the response currents of the three metal ions gradually increased. 3+ When the concentration increases further, the response current begins to decrease. 3+ When the concentration is lower than 2.4 mg / L, the thickness of the deposited bismuth film is insufficient, resulting in an insignificant catalytic effect. 3+ When the concentration exceeds 2.4 mg / L, the excess bismuth film will inhibit the NH2-alk-Ti3C2T x@N-CNTs catalytic performance. Therefore, considering the preparation of electrochemical sensors containing bismuth films, Bi 3+ The concentration affects the thickness of the formed bismuth film, which in turn affects the response current. 3+ concentration as the most preferred condition.

[0158] [Evaluation of the influence of pH value of the solution to be tested]

[0159] According to the detection method of this application example, a sample containing heavy metal ions Zn is prepared. 2+ or Cd 2+ or Pb 2+ The solution to be tested was adjusted to pH 3, 4, 5, 6 and 7, and the concentration of heavy metal ions was 1 μM; the electrochemical sensor of Example 5 was used as an electrode, and DPSV test was performed in the solutions to be tested with different pH values, and the deposition potential was set to -1.2 V, the pulse amplitude was 0.05 V, the pulse period was 0.5 s, and the deposition time was 700 s.

[0160] like Figure 6b As shown in the figure, as the pH value increases from 3.0 to 5.0, the response currents of the three heavy metal ions gradually increase, and then gradually decrease when the pH value increases from 5.0 to 7.0. The reason is that in the detection solution with a lower pH value, Bi / NH2-alk-Ti3C2T x @N-CNTs / GCE is easily protonated, resulting in the active sites of some heavy metal ions being + When the pH value is higher than 5.0, the metal ions tend to hydrolyze into hydroxides, which is not conducive to the enrichment of the three metal ions. Therefore, considering that the pH value of the solution to be detected is an important parameter that can directly affect the properties and state of the working electrode and the detected metal ions, the present invention takes the pH value of the solution to be detected = 5.0 as the most preferred condition.

[0161] [Evaluation of the influence of DPSV deposition time]

[0162] According to the detection method of this application example, a 2+ or Cd 2+ or Pb 2+ The solutions to be tested have a pH of 5 and a concentration of heavy metal ions of 1 μM. The electrochemical sensor of Example 5 is used as an electrode to carry out DPSV test in each solution to be tested. The deposition potential is set to -1.2 V, the pulse amplitude is 0.05 V, the pulse period is 0.5 s, and the deposition time is adjusted to 100 s, 200 s, 300 s, 400 s, 500 s, 600 s, 700 s and 800 s, respectively.

[0163] like Figure 6c As shown in Figure 2, as the deposition time increases, the current response of the target metal ions gradually increases and reaches a peak at 700 s. As the deposition time further increases, the response current remains relatively stable, which is due to the fact that NH2-alkTi3C2T x The gradual saturation of the binding sites on the surface of @N-CNTs / GCE. Therefore, considering that the deposition time directly determines the enrichment (deposition) degree of the target metal ions, the present invention takes the deposition time of 700s as the most preferred condition.

[0164] [Evaluation of the influence of DPSV deposition potential]

[0165] According to the detection method of this application example, a sample containing heavy metal ions Zn is prepared. 2+ or Cd 2+ or Pb 2+ The solution to be tested has a pH of 5 and a concentration of heavy metal ions of 1 μM. The electrochemical sensor of Example 5 is used as an electrode to carry out a DPSV test in the solution to be tested. The pulse amplitude, pulse period, and deposition time are set to 0.05 V, 0.5 s, and 700 s, and the deposition potentials are adjusted to -1.4 V, -1.3 V, -1.2 V, -1.1 V, and -1.0 V, respectively.

[0166] like Figure 6d As shown, as the deposition potential moves from -1.0V to -1.2V, the response current of the three metal ions increases. This increase can be attributed to the promotion of metal ion reduction as the deposition potential decreases. However, when the deposition potential is reduced from -1.2V to -1.4V, the response current decreases. This is because further reducing the deposition potential will enhance the hydrogen evolution reaction, thereby hindering the deposition of metal ions. Therefore, the present invention takes the deposition potential of -1.2V as the most preferred condition.

[0167] [Detection of Zn alone 2+ or Cd 2+ or Pb 2+ Performance evaluation of

[0168] According to the detection method of this application example, a sample containing heavy metal ions Zn 2+ or Cd 2+ or Pb 2+ The solution to be tested has a pH of 5, and each test solution has a different concentration of heavy metal ions; the electrochemical sensor of Example 5 is used as an electrode, and a DPSV test is performed in each solution to be tested, and the deposition potential is set to -1.2V, the pulse amplitude is 0.05V, the pulse period is 0.5s, and the deposition time is 700s.

[0169] like Figure 7a , Figure 7b and Figure 7c As shown in the figure, the response current of the three metal ions increases linearly with the increase of ion concentration, and the concentration range corresponding to the linear detection is 0.035~1.350μM (Zn 2+ )、0.025~1.900μM(Cd 2+ ) and 0.015~2.100μM(Pb 2+ ). The linear regression equation is as follows: Ip = 0.2549 + 3.6234c (R 2 =0.9950)(Zn 2+ )、Ip=1.3250+7.3282c(R 2 =0.9945)(Cd 2+ )、Ip=2.8223+9.2607c(R 2 =0.9921)(Pb 2+ The detection limits (LODs) of the three heavy metal ions were 10.0 nM (Zn 2+ )、7.5nM(Cd 2+ ) and 3.5nM(Pb 2+ )(S / N=3).

[0170] In summary, the sensor demonstrated effective single-cell detection of Zn 2+ or Cd 2+ or Pb 2+ Excellent performance.

[0171] [Simultaneous detection of Zn 2+ 、Cd 2+ and Pb 2+ Performance evaluation of

[0172] According to the detection method of this application example, a sample containing heavy metal ions Zn 2+ 、Cd 2+ and Pb 2+ The solution to be tested has a pH of 5, but each test solution has a different concentration and total concentration of heavy metal ions; the electrochemical sensor of Example 5 is used as an electrode, and a DPSV test is performed in the solution to be tested, and the deposition potential is set to -1.2V, the pulse amplitude is 0.05V, the pulse period is 0.5s, and the deposition time is 700s.

[0173] like Figure 7d As shown in Figure 2, the response currents of the three metal ions also increase linearly with the increase of ion concentration, and the concentration range corresponding to the linear detection is 0.045-1.000 μM (Zn 2+ )、0.030~1.550μM(Cd 2+ ) and 0.025~1.950μM(Pb2+ ). The linear regression equations are Ip=0.1565+1.892c(R 2 =0.9949)(Zn 2+ )、Ip=0.9450+7.2063c(R 2 =0.9931)(Cd 2+ ) and Ip = 1.2425 + 7.7474c (R 2 =0.9942)(Pb 2+ At this time, the detection limits of the three heavy metal ions were 15nM (Zn 2+ )、9.5nM(Cd 2+ ) and 5.0nM(Pb 2+ )(S / N=3).

[0174] In summary, the sensor can also effectively detect Zn 2+ 、Cd 2+ and Pb 2+ .

[0175] [Reproducibility evaluation]

[0176] According to the detection method of this application example, a sample containing heavy metal ions Zn 2+ 、Cd 2+ and Pb 2+ The pH of the solution to be tested was 5, and the concentration of heavy metal ions was 1 μM. Four parallel electrochemical sensors Bi / NH2-alk-Ti3C2T x @N-CNTs / GCE was used as an electrode, and DPSV tests were carried out in the test solutions. The deposition potential was set to -1.2 V, the pulse amplitude was 0.05 V, the pulse period was 0.5 s, and the deposition time was 700 s.

[0177] like Figure 8a As shown, there was no significant difference in the response current of the four groups (P<0.05). The relative standard deviations (RSD) of the three metal ions were calculated to be 5.50% (Zn 2+ )、1.35%(Cd 2+ ) and 1.80%(Pb 2+ The results show that the electrochemical sensor has excellent reproducibility.

[0178] [Repeatability evaluation]

[0179] According to the detection method of this application example, a sample containing heavy metal ions Zn 2+ 、Cd 2+ and Pb 2+The solution to be tested has a pH of 5 and a heavy metal ion concentration of 1 μM. The electrochemical sensor of Example 5 is used as an electrode, and nine consecutive DPSV tests are performed in the solution to be tested, with the deposition potential set to -1.2 V, the pulse amplitude set to 0.05 V, the pulse period set to 0.5 s, and the deposition time set to 700 s.

[0180] like Figure 8b As shown in the figure, there was no significant difference in the response current of the nine parallel tests (P<0.05). The results show that the sensor has excellent repeatability.

[0181] [Stability Assessment]

[0182] According to the detection method of this application example, a sample containing heavy metal ions Zn 2+ 、Cd 2+ and Pb 2+ The solution to be tested has a pH of 5 and a heavy metal ion concentration of 1 μM. The electrochemical sensor of Example 5 is stored at 4°C for 22 days, and is used as an electrode on different days within 22 days. A DPSV test is performed in the solution to be tested, and the deposition potential is set to -1.2 V, the pulse amplitude is 0.05 V, the pulse period is 0.5 s, and the deposition time is 700 s.

[0183] like Figure 8c As shown in Figure 2, the response currents of the three metal ions gradually decreased with the extension of storage time, which may be due to the damage of the composite film caused by long-term storage. 2+ 、Cd 2+ and Pb 2+ The response currents were 84.05%, 89.14% and 89.92% of the initial values ​​respectively. The results showed that the obtained electrochemical sensor has excellent storage stability.

[0184] [Anti-interference evaluation]

[0185] According to the detection method of this application example, a sample containing heavy metal ions Zn 2+ 、Cd 2+ and Pb 2+ The pH of the solution to be tested is 5, Zn 2+ 、Cd 2+ and Pb 2+ The concentration of heavy metal ions is 0.5 μM, and the concentration of Mg is 5 μM. 2+ , Ca 2+ 、Na + 、Al 2+ , Fe 3+ 、Co 2+ , Mn2+ Cu 2+ Any one of them. The electrochemical sensor of Example 5 was used as an electrode, and nine consecutive DPSV tests were performed in the solution to be detected, with the deposition potential set to -1.2 V, the pulse amplitude to 0.05 V, the pulse period to 0.5 s, and the deposition time to 700 s.

[0186] like Figure 8d As shown, except for Cu 2+ In addition, the presence of other interfering ions does not significantly affect the response currents of the three target metal ions. 2+ When 2+ )、52.32%(Cd 2 + ) and 41.10% (Pb 2+ ), this is because Cu 2+ Compete with the target heavy metal ions for binding sites, thus affecting the enrichment of metal ions. In this regard, K4Fe(CN)6 can be added to effectively eliminate Cu 2+ interference.

[0187] Application Example 2

[0188] This application example provides a method for detecting heavy metal ions in a compound seasoning, and the detection method comprises:

[0189] S1. Pre-treat the raw material samples of two compound seasonings A and B used for marinating casual sauce-marinated foods: First, transfer each raw material sample (1 g) to a 25 mL polytetrafluoroethylene digestion container, then mix with 14 mL of HNO3 / H2O2 (6:1, volume ratio), seal and let stand overnight; then put the digestion container into a microwave digestion oven for microwave digestion, heating at 120°C for 5 min; heating at 160°C for 10 min; heating at 180°C for 20 min. Subsequently, heat the sample solution to a final volume of 2 mL to obtain a digestion solution;

[0190] S2. 1 mL of the digestion solution is diluted to 25 mL with 0.2 mol / L ABS to obtain the solution to be tested;

[0191] S3. Using the electrochemical sensor obtained in Example 5 as an electrode, a DPSV test was performed in the solution to be detected to obtain a heavy metal ion response signal, and the detection potential range was set to -1.25 to -0.4 V, the deposition potential to -1.2 V, the pulse amplitude to 0.05 V, the pulse period to 0.5 s, and the deposition time to 700 s.

[0192] Comparative application example 1

[0193] This comparative application example 1 dilutes the other 1mL of digestion solution obtained in step S1 of application example 2 to 25mL with ultrapure water for ICP-MS experiment as comparative analysis. Before the ICP-MS experiment begins, the optimal experimental conditions of the instrument are determined using a calibration solution containing Li, Co, In, U, Ba, Bi and Ce (each element concentration is 10ng / mL). In order to eliminate non-spectral line interference during instrument operation, the internal standard solution containing Li, Sc, Ge, Y, In and Bi is automatically added online using the built-in program of the instrument. To ensure the accuracy of the analysis results, 66Zn, 111Cd and 208Pb were selected for detection.

[0194] Multiple tests were conducted in accordance with the standard addition recovery method, and the test results of Application Example 2 and Comparative Application Example 1 are listed in Table 1.

[0195] Table 1

[0196]

[0197] Note: “-” in Table 1 means no calculation is required; “RSD” is the relative standard deviation.

[0198] From Table 1 we can see that:

[0199] In the detection of raw material samples of compound seasoning A, Zn 2+ 、Cd 2+ and Pb 2+ The recoveries were 102.22% to 107.30%, 102.57% to 105.31% and 102.65% to 106.03% respectively, and the relative standard deviations (RSD) were all less than 3.57%. 2+ 、Cd 2+ and Pb 2+ The recoveries were 103.89% to 106.87%, 104.25% to 106.36% and 103.87% to 106.70%, respectively, and the relative standard deviations (RSDs) were all less than 4.27%. According to Table 1, the detection results obtained by the electrochemical method were consistent with those of ICP-MS, proving that Bi / NH2-alk-Ti3C2T x @N-CNTs / GCE electrochemical sensor has high accuracy and sensitivity in detecting heavy metal ions in raw material samples of compound seasoning. In addition, compared with ICP-MS, the Bi / NH2-alk-Ti3C2T x The electrochemical method of @N-CNTs / GCE not only has a simpler experimental process and a shorter detection time, but also has economic advantages. x@N-CNTs / GCE electrochemical sensor for detecting Zn in compound seasonings 2+ 、Cd 2+ and Pb 2+ It has great potential for practical application.

[0200] The present invention proposes a sensor based on amino-functionalized alkaline MXene nitrogen-doped carbon nanotubes and bismuth film, which can effectively detect Zn in composite seasonings simultaneously. 2+ 、Cd 2+ and Pb 2+ Among the components of the composite material, NH2-alk-Ti3C2T x It has a wide surface area and abundant functional groups, which helps to bind with target metal ions. x The outer layer is covered with nitrogen-doped carbon nanotubes, which enhance the conductivity and provide more active binding sites. The bismuth film enhances the binding ability with the target metal ions and promotes the enrichment of metal ions. In addition, the synergistic effect between the different materials further improves the electrochemical performance, enabling the sensor to sensitively and accurately detect the three metal ions. Under the optimized conditions, the detection limits of the three metal ions were 15nM (Zn 2+ )、9.5nM(Cd 2+ ) and 5.0nM(Pb 2+ ). The sensor has effectively detected Zn in the raw material samples of compound seasonings. 2+ 、Cd 2+ and Pb 2+ , and obtained satisfactory recoveries (102.22% to 107.30%) and low relative standard deviations (no more than 4.27%). In conclusion, this accurate, sensitive, simple and economical electrochemical sensor is very suitable for detecting Zn 2+ 、Cd 2+ and Pb 2+ It has broad application prospects.

[0201] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0202] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0203] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. An electrochemical sensor, characterized in that The invention comprises an electrode substrate and an electrode material layer arranged thereon, wherein the electrode material of the electrode material layer comprises a composite material obtained by coating an amino-functionalized alkaline MXene material with nitrogen-doped carbon nanotubes.

2. The electrochemical sensor according to claim 1, characterized in that The electrode material further includes a bismuth film, and the bismuth film covers the composite material; Preferably, the electrode substrate comprises a glassy carbon electrode; Preferably, the amino-functionalized alkaline MXene material comprises amino-functionalized alkaline Ti3C2T x .

3. A method for preparing an electrochemical sensor according to claim 1, characterized in that: The preparation method comprises: (1) mixing and dispersing an amino-functionalized alkaline MXene material and nitrogen-doped carbon nanotubes in a medium solvent, so that the nitrogen-doped carbon nanotubes cover the amino-functionalized alkaline MXene material to generate a composite material, and obtaining a mixed dispersion; (2) Using the mixed dispersion to form an electrode material layer on an electrode substrate to obtain an electrochemical sensor.

4. The method for preparing an electrochemical sensor according to claim 3, characterized in that: The preparation method further comprises, in step (1), first dispersing the nitrogen-doped carbon nanotubes in the medium solvent to obtain a dispersion, and then adding the amino-functionalized alkaline MXene material to the dispersion to perform the mixing and dispersion; Preferably, the mass ratio of the nitrogen-doped carbon nanotubes to the amino-functionalized alkaline MXene material is (3-6):1; Preferably, the medium solvent includes N,N-dimethylformamide; Preferably, the mixing and dispersing method includes ultrasound, and the time is 50 to 70 minutes; Preferably, in the mixed dispersion, the mass concentration of the composite material is 0.8-1.2 mg / mL.

5. The method for preparing an electrochemical sensor according to claim 3 or 4, characterized in that: The method for preparing the amino-functionalized alkaline MXene material in step (1) comprises providing an initial MXene material, first alkalizing the initial MXene material to obtain an alkaline MXene material, and then amino-functionalizing the initial MXene material to obtain an amino-functionalized alkaline MXene material; Preferably, the initial MXene material comprises Ti3C2T x ; Preferably, the alkalization method comprises: first mixing and stirring the initial MXene material and the base in a first solvent, and first washing and first drying the product to obtain the alkaline MXene material; Preferably, the first solvent comprises water; Preferably, the alkalization method further comprises: first preparing the first solvent and the base into an alkaline solution, and then performing the first mixing and stirring of the initial MXene material and the alkaline solution; Preferably, the alkaline solution comprises a NaOH solution with a mass percentage concentration of 3% to 8%; Preferably, the temperature of the first mixing and stirring is 20-30°C and the time is 3-5h; Preferably, the first washing method comprises washing at least three times with the first solvent; Preferably, the first drying method comprises vacuum drying at 40 to 60° C. for 8 to 12 hours; Preferably, the amino-functionalization method comprises: performing a second mixing and stirring of the obtained alkaline MXene material and APTES in a second solvent, performing a second washing and a second drying of the product, to obtain an amino-functionalized alkaline MXene material; Preferably, the amino functionalization method further comprises: first dispersing the obtained alkaline MXene material in a second solvent to obtain a suspension, then adding the APTES suspension to the suspension, and performing the second mixing and stirring; Preferably, the second solvent comprises ethanol and / or water; Preferably, the second solvent comprises ethanol and water in a volume ratio of (2-4):1; Preferably, the second mixing and stirring is performed at a speed of 400 to 600 rpm for 15 to 25 hours; Preferably, the second washing method comprises washing at least five times using the second solvent; Preferably, the second drying method comprises vacuum drying at 40-60° C. for 8-12 hours.

6. The method for preparing an electrochemical sensor according to any one of claims 3 to 5, characterized in that: The method for preparing the nitrogen-doped carbon nanotubes in step (1) comprises: performing a third mixing and stirring of the carbon nanotubes and the nitrogen source in a third solvent to obtain a suspension, performing a hydrothermal reaction on the suspension, and performing a third washing and a third drying on the product to obtain the nitrogen-doped carbon nanotubes; Preferably, the mass ratio of the carbon nanotubes to the nitrogen source is 1:(4-6); Preferably, the nitrogen source comprises urea; Preferably, the third solvent comprises water; Preferably, the temperature of the third mixing and stirring is 20-30°C and the time is 30-60min; Preferably, the temperature of the hydrothermal reaction is 160-180°C and the time is 12-16h; Preferably, the third washing method comprises washing at least five times using the third solvent; Preferably, the third drying method comprises vacuum drying at 70-90° C. for 12-20 hours.

7. The method for preparing an electrochemical sensor according to any one of claims 3 to 6, characterized in that: The preparation method further comprises, in step (2), dropping the mixed dispersion onto the surface of the electrode substrate, drying it to form the electrode material layer, and obtaining the electrochemical sensor; Preferably, the electrode substrate comprises a glassy carbon electrode; Preferably, the glassy carbon electrode is polished and cleaned before use; Preferably, the polishing and cleaning method comprises first polishing the deerskin cloth with aluminum oxide powder having a particle size of 0.04 to 0.06 μM, and then ultrasonically cleaning with nitric acid and water having a mass percentage concentration of 40% to 60% in sequence; Preferably, the drying temperature is 60-80° C. and the drying time is 5-20 min.

8. The method for preparing an electrochemical sensor according to any one of claims 3 to 7, characterized in that: The preparation method further comprises step (3), wherein step (3) comprises: using the electrochemical sensor obtained in step (2) as an initial electrode, electrochemically depositing the initial electrode in an electrolyte solution containing bismuth ions to generate a bismuth film and simultaneously coating the composite material to obtain an electrochemical sensor containing a bismuth film; Preferably, in step (3), the electrolyte solution comprises an acetic acid buffer solution with a concentration of 0.1 to 0.3 mol / L; Preferably, the concentration of bismuth ions in the bismuth ion-containing electrolyte solution is 0.6 to 3 mg / L, preferably 1.8 to 2.8 mg / L, and more preferably 2.2 to 2.6 mg / L; Preferably, the electrochemical deposition method comprises differential pulse stripping voltammetry; Preferably, the precipitation potential range of the electrochemical deposition is -1.4 to -1.0 V, more preferably -1.3 to -1.1 V; Preferably, the deposition time of the electrochemical deposition is 100 to 800 s, more preferably 300 to 750 s.

9. A method for detecting heavy metal ions in a compound seasoning, characterized in that: The detection method uses the electrochemical sensor according to claim 1 or 2 for detection, and the detection method comprises: S1. After mixing the raw material sample of the composite seasoning with the digestion solution, digestion is performed to obtain a digestion solution; S2. mixing the digestion solution with the electrolyte solution to obtain a solution to be tested; S3. Using the electrochemical sensor as an electrode, a differential pulse stripping voltammetry test is performed in the solution to be detected to obtain a response signal of the target heavy metal ion.

10. The detection method according to claim 9, characterized in that: In step S1, the compound seasoning contains natural spices; Preferably, the digestion solution comprises nitric acid and hydrogen peroxide in a volume ratio of (5-7):1; Preferably, the amount of the digestion solution is controlled to be 10 to 20 mL per gram of the raw material sample of the composite seasoning; Preferably, the digestion method comprises microwave digestion; Preferably, after the raw material sample of the compound seasoning is mixed with the digestion solution, it is sealed and allowed to stand before the digestion is performed; the sealed and allowed to stand time is 6 to 24 hours; Preferably, the microwave digestion process includes heating at 110-130°C for 3-7 min, then heating at 140-160°C for 8-12 min, and then heating at 180-200°C for 15-25 min; Preferably, in step S2, the electrolyte solution comprises an acetic acid buffer solution with a concentration of 0.1 to 0.3 mol / L; Preferably, the volume ratio of the digestion solution to the electrolyte solution in the solution to be detected is 1:(20-30); Preferably, the pH of the solution to be detected is 3 to 7; Preferably, in step S3, the detection potential range of the differential pulse stripping voltammetry test is -1.5 to 0 V, preferably -1.25 to -0.4 V; Preferably, the target heavy metal ions include Zn 2+ 、Cd 2+ or Pd 2+ At least one of .